Molecular Mismatch Predicts T Cell–Mediated Rejection and De Novo Donor‐Specific Antibody Formation After Living Donor Liver Transplantation. Issue 11 (23rd August 2021) - Ono, Kosuke; Ide, Kentaro; Tanaka, Yuka; Ohira, Masahiro; Tahara, Hiroyuki; Tanimine, Naoki; Yamane, Hiroaki; Ohdan, Hideki
Abstract : Human leukocyte antigen (HLA) molecular mismatch (MM) analysis improves the prediction of clinical outcomes in kidney transplantation compared with prediction via traditional antigen MM. However, it remains unclear whether the level of MM can be used for risk stratification among liver transplantation (LT) recipients. A retrospective observational study of 45 living donor LTs was performed to evaluate eplet MM as a risk factor for both T cell–mediated rejection (TCMR) in the first month and de novo donor‐specific antibody (dnDSA) formation. A total of 9 (20%) patients displayed TCMR. HLA‐A, HLA‐B, HLA‐C, and HLA‐DRB1 eplet MM numbers were not associated with TCMR. By contrast, HLA‐DQB1 eplet MM (DQB1‐EpMM) number was significantly high in patients with TCMR. The predicted indirectly recognizable HLA epitopes (PIRCHE‐II) score for the HLA‐DQB1 locus (DQB1‐PIRCHE‐II) was also significantly higher in the TCMR group than in the no‐TCMR group. There was a high probability for TCMR to occur with either a DQB1‐EpMM ≥7 or a DQB1‐PIRCHE‐II ≥13. Pretransplant mixed lymphocyte response analyses indicated that there were no significant differences between the antidonor T cell proliferation activities of patients with low‐number (<7) and high‐number (≥7) DQB1‐EpMMs. However, the proportion of CD25 expression on proliferating antidonor CD8 + T cells, used as a cytotoxic activity marker, was high in DQB1‐EpMMs ≥7. Moreover, both DQB1‐EpMMs ≥9 and DQB1‐PIRCHE‐II ≥3 were predictors of dnDSA formation. Thus, MM analysis may be applied toward tailored immunosuppression based on individual risks.